2020
DOI: 10.1016/j.amjmed.2019.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Direct-to-Consumer Genetic Testing Results Among Identical Twins

Abstract: Purpose: To evaluate the consistency of 3 commonly used direct to consumer genetic testing kits.Background: Genetic testing kits are widely marketed by several companies but the consistency of their results is unclear. Since identical twins share the same DNA, their genetic testing results should provide insight into test consistency.Methods: 42 identical twins (21 pairs) provided samples for three testing companies. Outcomes were concordance of ancestry results when i) twin pairs were tested by the same compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…23andMe reported 95.1% Chinese; 2.1% Filipino and Austronesian; 0.5% Indonesian, Thai, Khmer, and Myanma; AncestryDNA reported 100% China; Gencove reported 91% East Asia and 9% Southeast Asia. The general concordance regarding major contributors to ancestry and variability regarding minor contributors to ancestry is consistent with other studies showing congruent results for the major contributors to ancestry (Thompson, 2018) despite variability when considering all reported ancestral components (Huml et al., 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…23andMe reported 95.1% Chinese; 2.1% Filipino and Austronesian; 0.5% Indonesian, Thai, Khmer, and Myanma; AncestryDNA reported 100% China; Gencove reported 91% East Asia and 9% Southeast Asia. The general concordance regarding major contributors to ancestry and variability regarding minor contributors to ancestry is consistent with other studies showing congruent results for the major contributors to ancestry (Thompson, 2018) despite variability when considering all reported ancestral components (Huml et al., 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In the foreseeable future, one needs to consider the scenario where two services provide conflicting results. Previous studies also reported that differences in the choice of SNPs on microarrays used by different companies could be an important contributor to variability in disease risk (Imai et al., 2011) and variability in self‐reported phenotypic traits versus genetic testing results (Huml, Sullivan, Figueroa, Scott, & Sehgal, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate test results can lead to emotional distress, unnecessary diagnostic testing, and medical intervention, which may pose risks for patients. In one study, 40% of genetic variants reported in DTC DNA raw data were reportedly found to be false positives (Tandy-Connor et al, 2018) and considerable variation has been found when comparing results from different DTC DNA companies (Huml et al, 2020). Others who have questioned the predictive validity of DTC DNA results (Friez, 2018;Huml et al, 2020;Nelson et al, 2019;Tandy-Connor et al, 2018) highlighted concerns over reliability, consistency, and accuracy (United States Government Accountability Office 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, accuracy is strongly affected by the choice of reference populations and the selection and number of SNVs, all of which vary among ancestry testing companies. Consequently, it is not unusual for different companies to report somewhat different ancestral profiles for the same DNA sample . Furthermore, many human populations have migrated considerably during their history; therefore, modern-day samples represent a static and potentially inaccurate portrayal of a region’s inhabitants in the past.…”
Section: How It Workmentioning
confidence: 99%